2015
DOI: 10.1111/imj.12843
|View full text |Cite
|
Sign up to set email alerts
|

Indwelling peritoneal catheters in patients with cirrhosis and refractory ascites

Abstract: In ESLD patients who received an indwelling peritoneal catheter, there was 10% risk of developing BP and significant mortality increase. Though placing drains is not the mainstay of treatment for refractory ascites, we confirm the theoretical adverse risk of peritoneal drains on infection and survival in cirrhotics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
22
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 24 publications
0
22
1
Order By: Relevance
“…Both cases of minor bleeding responded to local pressure for 10 min to the insertion site with no recurrence. The mortality also did not seem to be affected by drain placement with average survival being around 22 months after drain placement varying in different patients according to the severity of their respective MELD scores (11). …”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations
“…Both cases of minor bleeding responded to local pressure for 10 min to the insertion site with no recurrence. The mortality also did not seem to be affected by drain placement with average survival being around 22 months after drain placement varying in different patients according to the severity of their respective MELD scores (11). …”
Section: Discussionmentioning
confidence: 96%
“…In addition, concerns have been raised regarding the risk of bacterial peritonitis with the use of indwelling peritoneal catheters (11, 12, 15). Recently, a retrospective observational study reported the risk of secondary bacterial peritonitis as high as 10% in patients with indwelling peritoneal catheters.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Hospice care is a distinctive and small program of PC offered to patients with an estimated life expectancy of 6 months or less when curative therapy is no longer the focus of treatment. Again, referral is often delayed for patients with ESLD, with 1 study reporting that 22% of patients admitted with liver and biliary disease died within 7 days of admission to hospice, compared with an overall mean early mortality of 15% . Short survival after admission to a hospice may indicate that hospice providers have not had sufficient time to identify the care needs and devise an optimal management plan, and it also suggests that patients may have received an unnecessary aggressive treatment course.…”
Section: Hospicementioning
confidence: 99%